Evaluasi Kinerja Layanan Kesehatan di UPTD Puskesmas Sidomulyo, Kecamatan Gading Cempaka, Kota Bengkulu - Hestiana, Agustri (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
The purpose of this study was to analyze the quality of healthcare services at the Sidomulyo Community Health Center (UPTD) in Gading Cempaka District, Bengkulu City, and to determine the factors contributing to public satisfaction as service users. This study used a qualitative, descriptive approach and was conducted from July to August 2024. Informants were selected using a purposive sampling method involving service providers (health center employees and administrative staff) and service recipients (patients/patients' families). Data collection was conducted using observation, structured interviews, and documentation. Data were analyzed using data reduction, data presentation, and conclusion drawing. To analyze service quality, researchers used five dimensions of service satisfaction (SERVQUAL): tangibles, responsiveness, reliability, assurance, and empathy. Overall, the results indicate that the quality of healthcare services at the Sidomulyo Community Health Center (UPTD) is quite good, with the highest scores being reliability, assurance, and empathy. However, several aspects still require improvement, particularly in the physical dimensions (availability of supporting facilities such as prayer rooms) and responsiveness (consistency of responsiveness and protection of staff). Factors related to service quality and community satisfaction include the competence and capabilities of healthcare workers, the availability of both physical and informational resources, the quality of interactions between healthcare workers and patients, and compliance with existing standards and regulations. This research is crucial as a foundation for ongoing improvements focused on strengthening facilities and infrastructure, services, communication, training, and regular performance evaluations to enhance the quality of healthcare services and make them more responsive to community needs.